Cultural content in Italian language textbooks published in Poland between the 19th and 20th centuries: A brief diachronic analysis - Kaliska, Marta (Kwartalnik Neofilologiczny, 2026)
This study examines cultural content evolution in Italian textbooks published in Poland (1841–1991). A qualitative analysis of four manuals reveals progression from 19th-century ethnographic stereotypes through literary canonization to post-war subjective narration and pragmatic-communicative approaches. Findings demonstrate how historical and sociopolitical factors influence content selection, reflecting paradigmatic shifts in foreign language pedagogy.